Two new species of Cabillus (Perciformes: Gobiidae) and the first record of Cabillus macrophthalmus from the Western Indian Ocean - Kovačić, Marcelo; Bogorodsky, Sergey V. (Zootaxa, 2013)
Two new species of the gobiid genus Cabillus, C. nigromarginatus sp. nov. and Cabillus nigrostigmus sp. nov. are described. Cabillus nigromarginatus (from Rodrigues, Western Indian Ocean) is distinguished from congeners by having 18–20 pectoral-fin rays; predorsal area naked; two scales with enlarged ctenii ventrally and dorsally at the caudal-fin base; head with anterior and posterior oculoscapular, and preopercular canals, with pores σ, λ, κ, ω, α, β, ρ, ρ1, ρ2, and γ, δ, ε respectively; the body with four midline lateral blotches, with two or three of them expanding upwards in dorsal saddles; a dark triangular blotch at caudal-fin base; and predorsal with pigmentation at lateral edges forming a rectangle. Cabillus nigrostigmus (from the Red Sea) is distinguished from its congeners by having 19 pectoral-fin rays; transverse scale series 7; nape scaled, median predorsal scales 7; body depth 5.8–6.0 in SL; snout length 1.5–1.9 in eye diameter; caudal-peduncle depth in its length 2.4–2.5; a broad dark brown bar below first dorsal fin beginning anteriorly at the level of fourth spine of the first dorsal fin; elongate black blotch along posterior half of first dorsal fin extending into the sixth spine and adjacent membranes; and midlateral black spot at the end of caudal peduncle followed by S-shaped dark bar. Cabillus macrophthalmus is recorded for the first time in the Western Indian Ocean (Red Sea and Seychelles) and redescribed.